If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 17a + 16b + 2c + 4c + -3b + -6a = 0 Reorder the terms: 17a + -6a + 16b + -3b + 2c + 4c = 0 Combine like terms: 17a + -6a = 11a 11a + 16b + -3b + 2c + 4c = 0 Combine like terms: 16b + -3b = 13b 11a + 13b + 2c + 4c = 0 Combine like terms: 2c + 4c = 6c 11a + 13b + 6c = 0 Solving 11a + 13b + 6c = 0 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-13b' to each side of the equation. 11a + 13b + -13b + 6c = 0 + -13b Combine like terms: 13b + -13b = 0 11a + 0 + 6c = 0 + -13b 11a + 6c = 0 + -13b Remove the zero: 11a + 6c = -13b Add '-6c' to each side of the equation. 11a + 6c + -6c = -13b + -6c Combine like terms: 6c + -6c = 0 11a + 0 = -13b + -6c 11a = -13b + -6c Divide each side by '11'. a = -1.181818182b + -0.5454545455c Simplifying a = -1.181818182b + -0.5454545455c
| 14*4+4*x=138 | | 6x+9=2x+24 | | 6x-6=3x+10 | | x^3-7x^2-22x+56=0 | | 3d-3=1.45 | | 4+35x=20x+28 | | 3*6/12 | | cos^2x=0.2 | | 5xsquare-x-12=4xsquare-6 | | 3x6/12 | | 3x6/12= | | -4(y-3)+7+5y=21 | | 6x+36=18 | | -16x^3y^2-8x^2y-24x^4y^4-40x^2y^3=0 | | (5x+6)+(-x+8)= | | 1/6•5/12 | | 4(x)+3=15 | | 96.822/2.7 | | 8x-4x-7x= | | -3x+2y=5fory | | 7m-13=54 | | (7y+4)-(y-2)= | | 5y+11=111 | | -9a^2-12ab+15a^3b^2-24ab^3=0 | | 15=3(2-4x) | | -4x-2=-3x+5 | | 4(a+2)=14-2(3*2a) | | 52+x^2+x=10 | | -4w-2=-3x+5 | | 12x^2-12x-9=0 | | 34=2x+3y | | x^2+8x-7=2x-11 |